1993
DOI: 10.1063/1.110249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatment on visible luminescence of porous silicon: Correlation with hydrogen and oxygen terminators

Abstract: The effect of hydrogen and oxygen surface termination atoms on the visible luminescence of porous Si was investigated for underlying physical mechanism. Atmospheric thermal treatment up to 1000 °C was carried out to study the functional relationship between the surface coverage and photoluminescence (PL). The results show that oxygen incorporation induces surface modification that enhance the PL efficiency after the removal of all SiHx (x=1–3) species. The presence of oxygen atoms can also account for the obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 14 publications
1
56
0
Order By: Relevance
“…The blue shift arises from an effective decrease in the size of the crystalline portion of the Si nanoparticles and nanowires within the pSi network as the surface of these species is progressively oxidized. [43][44][45][46][47][48] Previously, O 3 oxidation was studied by monitoring PL and IR results to determine whether there are any significant correlations. 34 An apparent correlation was found between the PL intensity and the O 2 SiH band amplitude.…”
Section: Resultsmentioning
confidence: 99%
“…The blue shift arises from an effective decrease in the size of the crystalline portion of the Si nanoparticles and nanowires within the pSi network as the surface of these species is progressively oxidized. [43][44][45][46][47][48] Previously, O 3 oxidation was studied by monitoring PL and IR results to determine whether there are any significant correlations. 34 An apparent correlation was found between the PL intensity and the O 2 SiH band amplitude.…”
Section: Resultsmentioning
confidence: 99%
“…As for the surface oxidation of PS, the thermal annealing effect has been investigated at various temperatures [2][3][4][5]. Tsai PS due to presence of oxygen atoms after the removal of Si-H x (x ¼ 1-3) species during annealing increases the PL intensity.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of a stable and efficient luminescent PS element into a microelectronic circuit encourages the possibility of commercial applications significantly. Regarding the PL of PS layers, thermal annealing treatments have been demonstrated to achieve strong and stable PL intensity [2][3][4][5]. Further the laser heating effect similar to the annealing has been introduced [6][7][8].…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, those oxidation methods can also improve the efficiency of light emission. Meanwhile, the blue shift [9] or red shift [10] of emission band and the increase [11] or decrease [12] of the band intensity was reported after different oxidation. However, it has been not reported that plasma enhanced chemical vapor deposition (PECVD) technique was used to oxide PS.…”
Section: Introductionmentioning
confidence: 96%